Differences in Fine Motor Development Before and After Playing Playdough in Children Preschool Children (5-6 Years Old) - Ningsih, Nurwati (Health Frontiers: Multidisciplinary Journal for Health Professionals, 2023)
Fine motor in preschoolers age 5-6 years old is very important to complete various activities. Stimulus is one of the factors that influence the development of fine motor, one of them is playing playdough. The purpose of this study is to determine the difference in fine motor development before and after playing playdough in preschoolers (5-6 years old). Pre eksperimental with One Group Pretest Posttest Design was used in this research. 30 children age 5-6 years old selected by using Purposive Sampling technic. To collecting data, the researchers use Denver II before and after the given intervention playing playdough. Intervention play playdough is done 3 times a week for 3 weeks with duration of play 60 minutes. The statistic test used in this study was Wilcoxon.The result of the research show that 11 children has an increase fine motor development after given intervention playing playdough. The result of the test statistic showed p value = 0,001, there is the difference in fine motor development before and after playing playdough in preschoolers (5-6 years old). The conclusion in this study is playing playdough can increasing fine motor development. Stimulus given correctly, consistently, and integration can create the development of fine motor children become optimum.